Contributions of substorm injections to SYM‐H depressions in the main phase of storms. Issue 12 (3rd December 2016) - He, Zhaohai; Dai, Lei; Wang, Chi; Duan, Suping; Zhang, Lingqian; Chen, Tao; Roth, I.
Abstract: Substorm injections bring energetic particles to the inner magnetosphere. But the role of the injected population in building up the storm time ring current is not well understood. By surveying Los Alamos National Laboratory geosynchronous data during 34 storm main phases, we show evidence that at least some substorm injections can contribute to substorm‐time scale SYM‐H / Dst depressions in the main phase of storms. For event studies, we analyze two typical events in which the main‐phase SYM‐H index exhibited stepwise depressions that are correlated with particle flux enhancement due to injections and with AL index. A statistical study is performed based on 95 storm time injection events. The flux increases of the injected population (50–400 keV) are found proportional to the sharp SYM‐H depressions during the injection interval. By identifying dispersionless and dispersive injection signals, we estimate the azimuthal extent of the substorm injection. Statistical results show that the injection regions of these storm time substorms are characterized with an azimuthal extent larger than 06:00 magnetic local time. These results suggest that at least some substorm injections may mimic the large‐scale enhanced convection and contribute to sharp decreases of Dst in the storm main phase. Key Points: Two case studies and statistical results of substorm injections in the main phase of storms are presented SYM‐H depressions are linearly correlated to particle injections due to substorms An estimation of the azimuthal extent of the particle injections is given